The effect of processing treatments on the shelf life and nutritional quality of green chilli (Capsicum annuum L.) powder - Sarker, Md. Sazzat Hossain; Hasan, S. M. K.; Aziz, Mohammad Gulzarul; Islam, M. Toihidul; Azam, S. M. R.; Roy, S.; Ibrahim, Mohd Nordin (Universiti Putra Malaysia Press, 2012)
An attempt was undertaken to investigate the effect of various common processing treatments, such as (a) without pedicle and cut longitudinally plus treated with 0.01% potassium metabisulphite (KMS), (b) without pedicle and sliced, (c) without pedicle as a whole, and (d) as a normal whole green chilli with pedicle, on the shelf life during storage in high density polyethylene (HDPE) and low density polyethylene (LDPE) packages at room temperature. The nutritional quality in terms of proximate compositions, Vitamin-C, beta-carotene and mineral contents of green chilli powder were also assessed. The chilli powder from the treatment (a) showed the highest stability up to 195 days in the HDPE pouches. In relation to proximate compositions and mineral contents, the processing treatments had a significant effect on them, except for Vitamin-C content at P<.0001. The results showed that the nutritional quality in all the samples of green chilli powder was better than that of the red chilli powder. Vitamin C content was reduced around 50% in all the samples due to the processing, while beta-carotene content was significantly increased as compared to the fresh green chilli. A simple calculation revealed the potential of green chilli powder as a value added and alternative spice.